Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko - Jurakić, Marko; Birkiđija Sotošek, Marina; Trinajstić, Maša; Kokot, Katja; Koščak, Marko (2025)
Strategies for Sustainable and Rural Development of the Cities of Sisak, Petrinja, and Hrvatska Kostajnica and the Municipalities of Majur and Topusko. The Sisak-Moslavina County in central Croatia, known for its rivers, forests, and cultural heritage, offers excellent potential for rural tourism. Despite challenges from the Homeland War and the 2020 earthquake, efforts focus on reconstruction and revitalisation of infrastructure, economy and tourism. In 2024, a group of students and professors from 12 universities in Croatia, Slovenia, and Serbia visited Sisak, Petrinja, Hrvatska Kostajnica, Topusko, and Majur to explore the tourism potential. Through guided tours and expert presentations, they identified potential for development and proposed solutions such as linking traditional and modern experiences, promoting eco-tourism, and improving digital marketing. All proposed projects are based on the principles of sustainable development and rural area valorisation. This publication is a result of a joint initiative by local stakeholders and the academic community. It highlights the region’s potential and provides strategic guidelines to support its long-term economic and social recovery through tourism.
Keywords: sustainable tourism, rural tourism, Sisak, Petrinja, Hrvatska Kostajnica, Topusko, Majur